2013
DOI: 10.1002/jcph.136
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Grapefruit Juice Eliminates Two Compound Classes as Major Mediators of the Grapefruit Juice–Fexofenadine Interaction: An In Vitro–In Vivo “Connect”

Abstract: The grapefruit juice-fexofenadine interaction involves inhibition of intestinal organic anion transporting polypeptide (OATP)-mediated uptake. Only naringin has been shown clinically to inhibit intestinal OATP; other constituents have not been evaluated. The effects of a modified grapefruit juice devoid of furanocoumarins (~99%) and polymethoxyflavones (~90%) on fexofenadine disposition were compared to effects of the original juice. Extracts of both juices inhibited estrone 3-sulfate and fexofenadine uptake b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…This is consistent with the findings of a previous study, which showed that the concentration of narirutin ranges from approximately 13 to 22% of that of naringin. 30 Although narirutin is one of the major components of grapefruit juice, 16,30 the contribution of narirutin to the inhibition of OATPs by grapefruit juice has not been quantitatively determined. It remains unclear how glycosyl moieties influence the OATP-inhibiting properties of flavanone derivatives and whether flavone glycosides generally inhibit OATPs more or less potently than their aglycones.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of a previous study, which showed that the concentration of narirutin ranges from approximately 13 to 22% of that of naringin. 30 Although narirutin is one of the major components of grapefruit juice, 16,30 the contribution of narirutin to the inhibition of OATPs by grapefruit juice has not been quantitatively determined. It remains unclear how glycosyl moieties influence the OATP-inhibiting properties of flavanone derivatives and whether flavone glycosides generally inhibit OATPs more or less potently than their aglycones.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Organic anion-transporting polypeptides (OATPs) belong to the solute carrier family and are involved in the intestinal absorption, tissue distribution, biliary excretion, and urinary elimination of drugs. , While OATP2B1 is regarded as the primary isoform responsible for the intestinal absorption of drugs, recent studies have demonstrated that OATP1A2 is also expressed in the intestines. , Therefore, these two OATPs have been increasingly focused on as targets of food–drug interactions in the intestines. Indeed, food–drug interactions involving grapefruit juice, orange juice, or other fruit juices have been reported for many OATP1A2 and/or OATP2B1 substrates, such as fexofenadine, talinolol, and aliskiren. In an in vivo study involving mice, it was shown that knocking out the mOatp2b1 gene, an ortholog of human OATP2B1, reduced the absorption of fexofenadine to the same extent as was seen in grapefruit juice-treated mice . Thus, food–drug interactions involving the inhibition of intestinal OATPs by fruit juices are attracting attention.…”
Section: Introductionmentioning
confidence: 99%
“…91 In vivo, concomitant administration of itraconazole, cyclosporine, ketoconazole, and verapamil increased the exposure of aliskiren by 6.33-, 4.79-, 1.76-, and 1.78-fold, respectively, indicating appreciable contributions of P-gp and CYP3A4 in the drug's disposition. [91][92][93][94][95] Overall, although other mechanisms such as inhibition of P-gp and CYP3A cannot be fully ruled out, the consistent decrease in aliskiren exposure observed when co-administered with 600 mL per day of apple, grapefruit, and orange juice, all known in vitro inhibitors of OATP2B1, 14,22,27,47,73,74,96,97 strongly support inhibition of OATP2B1 as the main mechanism of the clinical observations. Studies in patients with longer duration of administration of the juices would be valuable to quantify the potential effect of their co-administration on aliskiren efficacy.…”
Section: Aliskirenmentioning
confidence: 91%
“…When decreasing volumes of grapefruit juiceda total of 1200 mL (over 3 h), a single dose of 300 mL, and a single dose of 240 mL of grapefruit juicedwere co-administered with fexofenadine, the AUC of fexofenadine was reduced by approximately 60%, 67,71 40%, [69][70][71] and then only by about 24%, respectively. 73 These DDI observations with apple juice and grapefruit juice suggest that the interactions could be minimized by reducing the volume of juice consumed at once. In terms of enantiomers, exposures of both (R)-and (S)-fexofenadine were significantly decreased by 40% to 70% when co-administered with 400 mL of apple juice 74 or 250 mL of grapefruit juice.…”
Section: Fexofenadinementioning
confidence: 99%
“…When administered to healthy volunteers as an aqueous naringin solution (~1.2 m m ) or an equimolar concentration in grapefruit juice, naringin alone did not fully reproduce the decrease in the area under the concentration–time curve of the OATP substrate fexofenadine, suggesting that other constituents contribute to the effect of whole juice . A second clinical study involving a modified grapefruit juice devoid of furanocoumarins and polymethoxyflavones showed similar effects to the original grapefruit juice on the pharmacokinetics of fexofenadine , suggesting that flavanones are the major OATP inhibitors. Based on these clinical observations, constituents representative of the three chemical classes (Figure ) were tested to determine whether the proposed method could accurately identify and exclude clinically relevant OATP inhibitors.…”
Section: Introductionmentioning
confidence: 96%